Factors affecting sustainable rangeland management: Experts’ attitudes towards livelihood cornerstones in the Bazoft region - Gharibvand, Hojatollah Khedri; Azadi, Hossein; Dashtpagerdi, Mostafa Moradi; Ardali, Elham Omidezadeh; Witlox, Frank (European Journal of Sustainable Development, 2016)
Sustainable rangeland management (SRM) considers several dimensions of human life through recognition of sustainable livelihoods approach, in which livelihood cornerstones are acknowledged. In spite of this fact, research has not addressed this subject sufficiently. It has been recognized that analysis of the main drivers, allows for more appropriate strategies which are not the mere understanding of livelihoods, but rather ways towards sustainable development of rangelands. In this study, experts’ attitudes towards factors underpinning SRM were elicited. Data were collected using survey in order to analyze the livelihood cornerstones, in the Bazoft region in Chaharmahal and Bakhtiari province, Southwestern Iran. The participants were consulted to characterize the relative importance of each driver in approaching SRM. A five-point Likert scale was used to rank the three main influencing factors, including livelihood capital, vulnerability contexts as well as policies, institutions and processes (PIPs). We found that experts associated the main drivers with PIPs, vulnerability contexts and livelihood capital, respectively. Then, they prioritized policy, human capital and trends as the factors extracted from the main drivers in a more detailed assessment. Through these findings, we would offer policy makers should initially pay more attention to drivers that experts prioritized. Keywords: Sustainable development of rangelands, livelihood cornerstones, experts’ attitudes, human capital, policy, Bazoft region, Iran.